The impact of combining cetuximab with the traditional chemotherapy regimens on clinical effectiveness in metastatic colorectal cancer: a systematic review and meta-analysis - Marryam Azeem; Anees ur Rehman; Saba Rasheed; Aleena Shahzad; Muhammad Hamza Javed; Qurratul Ain Jamil; Hidayah Karuniawati; Saleh Karamah Al-Tamimi (BMC Cancer)
Abstract Background Metastatic colorectal cancer (mCRC) poses a high rate of morbidity and mortality despite various treatment advances. Cetuximab, an anti-EGFR, has shown promising efficacy in improving outcomes when combined with chemotherapy. Understanding its efficacy is essential for optimizing treatment strategies in mCRC. This systematic review and meta-analysis aims to evaluate the effectiveness of combining cetuximab with chemotherapy in mCRC. Methods PubMed and Google Scholar were systematically searched following the benchmarks indicated by PRISMA. The primary outcomes of the study were progression-free survival (PFS) and overall survival (OS). Statistical analyses were executed using Stata version 16. Results The meta-analysis encompassed 25 studies involving 3788 mCRC patients. The median age spans from 18 to 77 years. The cetuximab plus chemotherapy exhibited a higher PFS and OS with a significant difference (PFS: HR = 0.79, 95% CI = 0.63–0.96, p < 0.01, I2 = 38% and OS: HR = 0.78, 95% CI = 0.60–0.91, p < 0.01, I2 = 47%) compared to the control group. Subgroup analysis based on randomized controlled trials demonstrated consistent treatment effects for PFS (HR = 0.77, 95% CI = 0.62–0.93) and OS (HR = 0.76, 95% CI = 0.61–0.88) in the cetuximab treatment group. Conclusions Combining cetuximab with chemotherapy offers a potential benefit in improving survival outcomes for metastatic colorectal cancer patients, as indicated by this study. These results suggest that cetuximab may be a valuable addition to mCRC treatment strategies, warranting further clinical investigation and integration into standard care.